2020
DOI: 10.21037/jtd.2019.12.121
|View full text |Cite
|
Sign up to set email alerts
|

Sublobectomy versus lobectomy for long-term survival outcomes of early-stage non-small cell lung cancer with a tumor size ≤2 cm accompanied by visceral pleural invasion: a SEER population-based study

Abstract: Background: The optimal surgical strategy for early-stage non-small cell lung cancer (NSCLC) with visceral pleural invasion (VPI) remains unclear. Due to limited prospective comparative data for these surgical modalities, the objective of the current study was to compare the long-term survival outcomes of sublobectomy (Sub) versus lobectomy (Lob) for NSCLC with a tumor size ≤2 cm and VPI. Methods: Patients with early-stage NSCLC characterized by VPI diagnosed between 2004 and 2013 were identified from the Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Currently, anatomical surgical resection and mediastinal lymph node dissection are the most effective methods for treatment of early stage LUAC patients, and the main surgical procedures are lobectomy and sub-lobectomy ( Lin et al, 2020 ; Yu et al, 2020 ). Advanced-stage LUAC covers a variety of disease manifestations and has an equally complex range of multimodal treatment options, including systemic and local therapies (chemotherapy, radiation therapy, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Currently, anatomical surgical resection and mediastinal lymph node dissection are the most effective methods for treatment of early stage LUAC patients, and the main surgical procedures are lobectomy and sub-lobectomy ( Lin et al, 2020 ; Yu et al, 2020 ). Advanced-stage LUAC covers a variety of disease manifestations and has an equally complex range of multimodal treatment options, including systemic and local therapies (chemotherapy, radiation therapy, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Segmentectomy is an anatomical resection with extensive lymph node dissection, while wedge resection removes the lung tumor and normal lung parenchyma from the margin surrounding the lung (16). Sublobectomy is preferred for tumors ≤2 cm combined with adenocarcinoma in situ, ≥50% ground-glass appearance on CT, or a long doubling radiologic surveillance time (≥400 days) (17).…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Comprehensive Cancer Network (NCCN) Clinical Practice Guideline in Oncology for NSCLC, a sub-lobar resection can be performed in patients with a tumor size ≤2 cm combined with adenocarcinoma in situ (AIS) histology, ≥50% groundglass appearance on CT or a long doubling radiologic surveillance time (≥400 days) (17).…”
Section: Surgical Approachmentioning
confidence: 99%
“…Yu et al analyzed a cohort of 1,386 patients with NSCLC less than 2 cm in size and VPI; the analysis shows that patients treated with lobectomy had better OS and DFS than those who underwent sublobectomy (17). Several studies have shown the ability of VPI to cause malignant pleural effusions and higher mediastinal lymph node metastases, therefore surgical resection should also include extensive lymph node dissection in order to obtain better staging.…”
Section: Surgical Approachmentioning
confidence: 99%